Corporate social responsibility and firm performance Of licensed commercial banks in Sri Lanka - Balagobei, S.; Anandasayanan, S. (Macrothink Institute, 2018)
Corporate social responsibility (CSR) is a business approach that contributes to sustainable development by delivering economic, social and environmental benefits for all stakeholders. This concept has emerged over the past thirty years to occupy a significant role in certain aspects of the organizational theory. The purpose of this study is to examine the impact of CSR on firm performance from a developing country’s environment. This study considered only 12 licensed commercial banks as sample and obtained secondary data from the financial statements of the licensed commercial banks in Sri Lanka for the period of 2012-2016. Consequently, the quantitative data were employed in the panel data regression model using E-Views software to scientifically analyse the data to identify the significant relationship between these two variables. The control variable is firm size, to be consistent with the previous studies in the literature review. The finding shows that there is no significant impact of social, economic and environmental variables on firm performance. Further the results reveal that there is a significant positive association between CSR and firm performance (ROA) whereas firm size has a negative association with firm performance (Tobin’s Q).The study illustrates and provides some insights and builds on the literature in the area of CSR in a developing country’s environment.
Keywords: Corporate social responsibility; Firm performance; Firm size